Mesenchymal stem cells therapy improves ovarian function in premature ovarian failure: a systematic review and meta-analysis based on preclinical studies - Guo, Congcong; Ma, Yubo; Situ, Yanqiu; Liu, Li; Luo, Guoqun; Li, Huan; Ma, Wenmin; Sun, Li; Wang, Wen; Weng, Qiuying; Wu, Linlin; Fan, Dazhi (Frontiers in Endocrinology, 2023)
Background Studies have revealed that the transplantation of mesenchymal stem cells (MSCs) might be a potential star candidate for premature ovarian failure (POF) in animal experiments. However, individual studies with a small sample size cannot be used to draw a clear conclusion. Therefore, we conducted a systematic review and meta-analysis to explore the potential of using MSCs in the treatment of POF in animals. Methods Seven databases were searched for studies exploring the effect of the transplantation of MSCs on POF in animal models. The PRISMA guideline was followed, and the methodological quality was ensured using SYRCLE’s risk of bias tool. RevMan 5.4 and STATA 12.0 software was performed to meta-analysis. Results In total, 37 studies involving 1,079 animals were included. Significant associations were found for MSCs with the levels of E2 (SMD 2.69 [95% CI 1.97, 3.41]), FSH (-2.02, [-2.74, -1.30]), primary follicles (2.04, [1.17, 2.92]), secondary follicles (1.93, [1.05, 2.81]), and primordial follicles (2.38, [1.19, 3.57]. Other outcomes, such as AMH, LH, INHB, antral follicles, growing follicles, mature follicles, and early antral were also found to be significant. There was no difference in FSH/LH, corpus leteum, follicles, and estruc cycle. Conclusions Our meta-analysis result indicated that the transplantation of MSCs might exert therapeutic effects on animal models of POF, and these effects might be associated with improving the disorder of the sexual cycle, modulating serum hormone expressions to a better state, and restoring ovarian function.